Pemberdayaan Kelompok Masyarakat Padatuo Kabupaten Bone Melalui Pelatihan Produksi Pakan Ternak Berbasis Limbah Kepiting Rajungan - Wahdaniar Wahdaniar; Nur Insani Amir; Rika Nurfiana (Jurnal Medika: Medika, 2025)
This community service program focused on utilizing swimming crab shell waste as an innovative solution to reduce livestock feed costs and environmental issue in the Padatuo community group, Bone regency. The activity aimed to enhance participants knowledge and skills in processing the waste into high-nutrient feed flour through practical simulation method. The approach involved three stages: (1) observation and needs analysis; (2) simulation of flour production including washing, boiling, drying and grinding; and (3) evaluation through pre-test and post test. The results showed a significant improvement in participants understanding, with post-test score (86.2) far higher than pre-test score (42.6). Participants successfully produced quality flour with fine texture, non offensive odor, and high mineral content. Economic impacts included up to 30% reduction in feed costs, while environmental benefits were achieved through waste reduction. This activity demonstrates that participatory simulation-based approach are effective in empowering communities and creating sustainable solution.